2018
DOI: 10.1111/ejss.12551
|View full text |Cite
|
Sign up to set email alerts
|

Linking diagnostic features to soil microbial biomass and respiration in agricultural grassland soil: a large‐scale study in Ireland

Abstract: The functional potential of soil ecosystems can be predicted from the activity and abundance of the microbial community in relation to key soil properties. When describing microbial community dynamics, soil physicochemical properties have traditionally been used. The extent of correlations between properties, however, differs between studies, especially across larger spatial scales. In this research we analysed soil microbial biomass and substrate‐induced respiration of 156 samples from Irish grasslands. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
9
0
2
Order By: Relevance
“…It is well known that Mg 2+ , together with other base cations, is an important soil nutrient that greatly influences the soil microbial population and their activity since it is required for microbial growth and protein synthesis (RUTGERS et al, 2009). The finding of a strong positive correlation between SMR and Mg 2+ was also detected by RICHTER et al (2018), who assessed the effect of diagnostic features, land use, and soil type on microbial biomass and microbial indices in Irish grassland. This study also found a positive correlation of K2O with SMR (r = 0.58; p < 0.05).…”
Section: Influence Of Lut On Smr and Major Drivers For Its Variabilitymentioning
confidence: 88%
“…It is well known that Mg 2+ , together with other base cations, is an important soil nutrient that greatly influences the soil microbial population and their activity since it is required for microbial growth and protein synthesis (RUTGERS et al, 2009). The finding of a strong positive correlation between SMR and Mg 2+ was also detected by RICHTER et al (2018), who assessed the effect of diagnostic features, land use, and soil type on microbial biomass and microbial indices in Irish grassland. This study also found a positive correlation of K2O with SMR (r = 0.58; p < 0.05).…”
Section: Influence Of Lut On Smr and Major Drivers For Its Variabilitymentioning
confidence: 88%
“…For soil pH, an optimum was assumed at a pH(H 2 O) of 6.5 [36,51,52]. For clay content, an optimum was assumed at 25% clay particles, as lower values show a decrease in fertility and microbial biomass [53], and higher values may lead to anaerobic conditions [54]. For bacterial functional diversity, 1-hillslope from the community-level physiological profile determined in Biolog plates-was used as a measure for richness [47].…”
Section: Modelling and Mapping Soil Biodiversity: Europementioning
confidence: 99%
“…Difference between predicted and observed values (expressed in fractions) for 11 biological attributes in 49 soil samples of the Province Noord-Brabant[54]). …”
mentioning
confidence: 99%
“…Chilena (Dube et al, 2009), pastizales de toda Irlanda (Richter et al, 2018), ecosistemas arbóreo de suelos arenosos (Lee y Jose, 2003) y la misma tendencia de correlación para pastizales templados (Cui y Holden, 2015). Estas relaciones observadas afirman la idea de que el C orgánico es de vital importancia para los microorganismos del suelo y su dependencia como fuente de recurso para la biota edáfica en diferentes ecosistemas.…”
Section: Carbono De La Biomasa Microbiana (C-bm)unclassified
“…Observamos que las mayores coberturas vegetales y precipitaciones en el sitio de la EMH se acompañaron con valores superiores de carbono orgánico del suelo, el cual es de vital importancia como fuente de recurso para la biota edáfica (Lauber et al, 2008;Richter et al 2018). Además, en las distintas áreas ecológicas, la respuesta positiva de la RBS fue atribuida al C-BM del suelo.…”
Section: Patagonia Surunclassified